Usulan Tata Letak Ulang Menggunakan Software Quantitative Systems untuk Meminimalkan Jarak Perpindahan Bahan di Lantai Produksi Departemen Mechanic PT Jefta Prakarsa Pratama - Khristian Edi Nugroho; Dimas Rahmawan; Prayogo Adi Utomo (ComTech: Computer, Mathematics and Engineering Applications, 2012)
The layout applied on the production floor of the Department of Mechanic of PT. Jefta Prakarsa Pratama is not considered as an optimal layout. The reason triggered this optimal level, are some backtrack movements that reduce the effectiveness and efficiency of material handling activities. This research refers to two types of calculation methods. First, manual calculation, which is rectilinear distance measure. Second, computerized calculation, which is Quantitative Systems (QS) software. There are three critical criterias referenced in this research, i.e. straight flow of material, more minimal backtrack movement, and more minimal material moving distance. The iteration results using QS software are translated into block layout and then are made as a proposed layout. The rectilinear calculations performed manually are intended to calculate the total of material moving distance. The data processing obtained a re-layout solution which is more optimal for the production floor of the Department of Mechanic, because it could reduce backtrack distance by 75.28% and the material moving distance by 30.03%. The implementation of the proposed layout is expected to reduce the time of material moving activity on the production floor of the Department of Mechanic, so that the material moving process could run more effectively and efficiently.